Dora, Hysteria and Gender : Reconsidering Freud's Case Study - Westerink, Herman, 1968-; Finzi, Daniela, 1976- (Figures of the unconscious, 2018)
'Dora' is one the most important and interesting case studies Sigmund Freud conducted and later described. It constitutes a key text in his oeuvre and finds itself at the crossroads of his studies in hysteria, the theory of sexuality and dream interpretation. The Dora case is both a literary and theoretically groundbreaking text and an account of a 'failed' treatment. In Dora, Hysteria and Gender renowned Freud scholars reflect on the Dora case, presenting various innovative and controversial perspectives and elaborating the significance of the text for contemporary debates on gender, sexuality and queer theory. This volume is of interest for psychoanalysts and scholars working on psychoanalysis, sexuality, gender, queer theory, philosophical anthropology and literary studies.